(untitled) (Journal of the College of Education for Women, 2019)
The study aims at identifying the morphological and psycho-socio-economic qualities wished to be in a life partner among a sample of Palestinian youth. The total sample was (231) and consisted of (83) male and (148) female students. Each student presented a detailed report on the qualities he/she wished to be in life partner. The study used the descriptive approach and content analysis method. The validity and stability of the analysis were calculated. The results showed eight qualities in both groups: physical, psychological, emotional, social, intellectual, familial, economic and academic. Female students were found to have more variations than male students in terms of the qualities preferable in the life partner. Male students were clearly in favor of certain qualities in female students, such as height, general appearance, eyes, hair, skin color, waist, face, body shape, weight, and chest size. The female life partner also has to be psychologically entertaining, emotionally romantic, socially outgoing, capable of raising children; having an economically appropriate condition, and academically uninterested in postgraduate studies. Similarly, female students had, to a large extent, clear and consistent views towards male students. They preferred certain qualities in male students such as height, face, general appearance, skin color, hair, weight, and body shape. The male life partner also has to be psychologically understanding, romantically outgoing, having a strong and interrelated family relationship, educated and a holder of a bachelor’s degree.